2019
DOI: 10.1007/s10461-019-02594-6
|View full text |Cite
|
Sign up to set email alerts
|

The People Living with HIV (PLHIV) Resilience Scale: Development and Validation in Three Countries in the Context of the PLHIV Stigma Index

Abstract: Supporting resilience among people living with HIV (PLHIV) is crucial to their sustained uptake of HIV services as well as psychological and social wellbeing. However, no measures exist to assess resilience specifically in relation to living with HIV. We developed the PLHIV Resilience Scale and evaluated its performance in surveys with 1207 PLHIV in Cameroon, Senegal and Uganda as part of the PLHIV Stigma Index—the most widely used tool to track stigma and discrimination among PLHIV worldwide. Factor analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Existing academic literature has reasonably established over the years that factors such as education, religion and spirituality, and social support from family and friends afford protective effects to gbMSM against the clinical and social impacts of HIV/AIDS, and consequently, foster their HIV resilience [16,[26][27][28]. Researchers have found that HIV education is a major factor that protects gbMSM from the impacts of HIV/AIDS by buffering the effects of elevated levels of sexual risk behaviors that are related to HIV infections [28].…”
Section: Considering and Valuing Established Protective Factors In The Development Of Interventions That Foster Resilience To Hiv/aidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing academic literature has reasonably established over the years that factors such as education, religion and spirituality, and social support from family and friends afford protective effects to gbMSM against the clinical and social impacts of HIV/AIDS, and consequently, foster their HIV resilience [16,[26][27][28]. Researchers have found that HIV education is a major factor that protects gbMSM from the impacts of HIV/AIDS by buffering the effects of elevated levels of sexual risk behaviors that are related to HIV infections [28].…”
Section: Considering and Valuing Established Protective Factors In The Development Of Interventions That Foster Resilience To Hiv/aidsmentioning
confidence: 99%
“…Much attention has focused on religion and spirituality as protective factors that foster resilience to HIV/AIDS among HIV-positive gbMSM. Researchers not only examined the perceived benefits of religious and spiritual coping as critical personal and social resources for older adults living with HIV/AIDS and an aging epidemic [30] but they also documented the importance of faith, spirituality, and practicing a religion as an important consideration for developing interventions that foster resilience to HIV/AIDS [26,27,31,32]. ASOs, LGBTQ+ agencies, and community-based groups have valued religion and spirituality as factors that offer protection against, and promote resilience to, the clinical and social impacts of HIV/AIDS.…”
Section: Considering and Valuing Established Protective Factors In The Development Of Interventions That Foster Resilience To Hiv/aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous resilience scales have not been specific to living with HIV. Only one scale (PozQoL) measures resilience in the context of HIV [24]; however, the authors indicate it may be too broad to be useful as a brief tool. The 10-item PLHIV-specific resilience scale by Gottert et al was found to have satisfactory psychometric properties and now forms part of the PLHIV Stigma Index 2.0 [25].…”
Section: Methodologies To Improve Implementation Science Research Andmentioning
confidence: 99%
“…Stigmatisation and resilience share many common features (Fig. 2), some of which are IBD specific, and it is reasonable to assume that they mutually influence each other, as shown for psychiatric illnesses [100] and patients living with HIV [101]. Disappointingly, only one study involving community-based adult patients with self-reported IBD has investigated this issue in the IBD population so far.…”
Section: Resilience In Inflammatory Bowel Diseasementioning
confidence: 99%